Selective glycerol esterification over organomontmorillonite catalysts - Tri Yogo Wibowo; Ridzuan Zakaria; Ahmad Zuhairi Abdullah (Universiti Kebangsaan Malaysia, 2010)
Organomontmorillonites were synthesized by grafting cationic surfactants i.e quaternary ammonium compounds into the interlayer space and were characterized using XRD, FTIR and N2 adsorption/ desorption analysis. The organomontmorillonites were applied as catalyst for the esterification of glycerol (GL) with lauric acid (LA). The catalyst which had symmetrical onium salts (tetrabuthylammoniumbromide, TBAB) gave higher activity than that of unsymmetrical onium salts (cetyltrimethylammoniumbromide, CTAB). Over the TBAB-montmorillonite catalyst, glycerol monolaurate was obtained with a selectivity of about 80%, a lauric acid conversion of about 71% and a glycerol monolaurate yield of about 57%.